2017
DOI: 10.1186/s12885-017-3599-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the clinicopathological and molecular characteristics of patients with suspected Lynch syndrome in Latin America

Abstract: BackgroundGenetic counselling and testing for Lynch syndrome (LS) have recently been introduced in several Latin America countries. We aimed to characterize the clinical, molecular and mismatch repair (MMR) variants spectrum of patients with suspected LS in Latin America. MethodsEleven LS hereditary cancer registries and 34 published LS databases were used to identify unrelated families that fulfilled the Amsterdam II (AMSII) criteria and/or the Bethesda guidelines or suggestive of a dominant colorectal (CRC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 75 publications
4
43
1
2
Order By: Relevance
“…41 Although their population prevalence is not well understood, founder mutations in MSH2 (c.1906G>C, p.A636P) and MSH6 (c.3959_3962delCAAG and c.3984_3987dupGTCA) appear to account for the majority of Lynch syndrome cases in individuals of Ashkenazi Jewish ancestry. 42,43 Additional data are identifying other candidate founder mutations in various populations with undefined prevalence, including Americans of German ancestry, 44 African Americans, 45 Latinos, 46 Poles, 47 and many other groups. 48 Founder mutations may account for a sizeable fraction of individuals with BMMRD syndrome, which is caused by biallelic inheritance of pathogenic germline variants in the same MMR gene.…”
Section: Epidemiology Of Lynch Syndromementioning
confidence: 99%
“…41 Although their population prevalence is not well understood, founder mutations in MSH2 (c.1906G>C, p.A636P) and MSH6 (c.3959_3962delCAAG and c.3984_3987dupGTCA) appear to account for the majority of Lynch syndrome cases in individuals of Ashkenazi Jewish ancestry. 42,43 Additional data are identifying other candidate founder mutations in various populations with undefined prevalence, including Americans of German ancestry, 44 African Americans, 45 Latinos, 46 Poles, 47 and many other groups. 48 Founder mutations may account for a sizeable fraction of individuals with BMMRD syndrome, which is caused by biallelic inheritance of pathogenic germline variants in the same MMR gene.…”
Section: Epidemiology Of Lynch Syndromementioning
confidence: 99%
“…These studies in Latin America have reported about 18% of patients diagnosed at a young age have pathogenic variants in genes not traditionally associated with CRC (e.g., ATM [OMIM #607585], CHEK2 [OMIM #604373], BRCA1 , BRCA2 , CDKN2A [OMIM #600160], PALB2 [OMIM #610355]). MHL1 (OMIM #120436) pathogenic variants were more frequent in patients from Peru, Mexico and Chile, whereas MSH2 (OMIM #609309) pathogenic variants occurred mostly in patients from Colombia and Argentina (Ñique Carbajal, Sánchez Renteria, Lettiero, Wernhoff, & Domínguez‐Valentin, ; Rossi et al, ).…”
Section: Healthcare Services Of Genetics and Genomicsmentioning
confidence: 99%
“…). MHL1 (OMIM #120436) pathogenic variants were more frequent in patients from Peru, Mexico and Chile, whereas MSH2 (OMIM #609309) pathogenic variants occurred mostly in patients fromColombia and Argentina (Ñique Carbajal, Sánchez Renteria, Lettiero, Wernhoff, & Domínguez-Valentin, 2014;Rossi et al, 2017).…”
mentioning
confidence: 99%
“…[12][13][14][15] Families that fulfilled the Amsterdam criteria and/or the Bethesda guidelines [16][17][18] Patients were informed about their inclusion into the registries and written informed consent was obtained from all participants during genetic counseling sessions. The data include results from germline DNA testing, tumor testing (based on microsatellite instability analysis and/or immunohistochemistry) and family history.…”
Section: South American Cancer Familiesmentioning
confidence: 99%
“…In these cases, it is possible to perform functional testing to assess the impact of a variant, which has frequently served to approach a classification for such variants. 12 In this work, we have tested nine small coding variants identified in 9 South American individuals. 11 Genetic counselling and testing has recently been introduced in Latin America and has led to the identification of several yet uncharacterized genetic variants in MLH1.…”
Section: Introductionmentioning
confidence: 99%